2009
DOI: 10.1007/s00125-009-1539-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential association of HLA with three subtypes of type 1 diabetes: fulminant, slowly progressive and acute-onset

Abstract: These data suggest that HLA associations with fulminant type 1 diabetes are qualitatively different from those with other subtypes of type 1 diabetes, whereas the HLA contribution to slowly progressive type 1 diabetes is qualitatively similar to, but quantitatively different from, that in acute-onset type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 20 publications
8
126
1
1
Order By: Relevance
“…The alleles and haplotypes associated with acute-onset and those associated with slowly progressive T1D are similar (14). Hashimoto et al (15) reported that the characteristics of susceptibility HLA haplotypes differed among patients with APS3v (T1D and GD), T1D alone and GD alone.…”
Section: Frequencies Of Antigen or Allele Controlmentioning
confidence: 94%
“…The alleles and haplotypes associated with acute-onset and those associated with slowly progressive T1D are similar (14). Hashimoto et al (15) reported that the characteristics of susceptibility HLA haplotypes differed among patients with APS3v (T1D and GD), T1D alone and GD alone.…”
Section: Frequencies Of Antigen or Allele Controlmentioning
confidence: 94%
“…We reported that the HLA-DRB1*04:05-DQB1*04:01 haplotype is associated with Japanese fulminant type 1 diabetes in a homozygous manner [14,15].…”
Section: Enterovirus In the Pancreasmentioning
confidence: 94%
“…These activated antigen-presenting cells could potentially activate preprimed autoreactive T cells, which can then initiate autoimmune response (bystander activation of autoreactive immune T cells) [43]. In addition to this mode of bystander activation of autoreactive T cells, virus-specific T cells are due to abundant lymphoplasmacytic inflammation to the exocrine pancreas [ [15]. The similarity of histological findings and genetic background and the high prevalence of impaired glucose tolerance and autoantibodies against amylase suggest that autoimmune mechanisms against amylase might have some common effects on the destruction of pancreatic islets and exocrine tissues in both fulminant type 1 diabetes and autoimmune pancreatitis.…”
Section: Bystander Activation/killing Of Islet Cells In Fulminant Typmentioning
confidence: 99%
“…However the degradation mechanism of cell in FT1DM of humans is unknown. Recently, it has been reported that the onset of FT1DM may be attributed to certain HLA subtype, to viral infection, or to pregnancy (Imagawa et al, 2003;Imagawa et al, 2005;Shimizu et al, 2006;Kawabata et al, 2009). In recent study, macrophages and T cells -but not natural killer cells -had infiltrated the islets and the exocrine pancreas and Toll-like receptor (TLR) 3, a sensor of viral components, was detected in most of macrophages and T cells in FT1DM patients (Shibasaki et al, 2010).…”
Section: Onset Of Fulminant Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…Insulitis with macrophage dominant infiltration was observed in IRS-2 deficient mice and human FT1DM. Destruction mechanism of cells associated HLA, viral infection and pregnancy were investigated in detail in human FT1DM patients (Kawabata et al, 2009;Murabayashi et al, 2009;Tan & Loh, 2010), whereas association with MHC was not investigated in IRS-2 deficient mice. Since FT1DM was observed in only male IRS-2 deficient mice, pregnancy is not associated with onset of FT1DM.…”
Section: Comparison Of Pathology Of Ft1dm Between Irs-2 Deficient Micmentioning
confidence: 99%